Analysis of the simulation of the PALM model for the Convective Boundary Layer in the Amazon (GOAMAZON 2014/5) - Carneiro, Rayonil Gomes (2020)
The present work had the objective to evaluate the development of the convective boundary layer in the Amazon region simulated by a high resolution Large Eddy Simulation model (named PALM model), for days representative for rainy and dry seasons. The study used data from the GOAmazon Project 2014/2015 (Green Ocean Amazon). Using data from radiosondes and Ceilometer as truth values, they were compared with the simulations performed through the PALM model. The results showed that, in general, the convective boundary layer cycle for the Amazon region was well represented by PALM model. It´s outputs has showed an overestimation of ≈ 35 m in a rainy day and an underestimation of ≈ 20 m in a dry day, both in development phase of the convective layer at late morning. It was also observed that the latent heat flux profile was higher than the sensible heat in the atmosphere, because it is a region with a lot of humidity, with the boundary layer responding rapidly to the maximum surface forcing.